Neurophysiological analysis of adaptation processes rhythmicity in athletes and subjects who practice relaxation: experimental study - Popova, T.; Koryukalov, Y.; Erlikh, V.; Kourova, O. (Medicina dello Sport, 2020)
BACKGROUND: The aim of this experimental study was to reveal the mechanisms of changes in EEG and functional parameters of the main systems of the body in people aged 18-30 during their adaptation to physical loads and regular relaxation exercises. METHODS: We examined three groups, consisting of students and postgraduate students of the university (mean age 24±3): group one that was made up of professional athletes; group two of those practicing relaxation; and group three of those practicing no relaxation nor playing any sport. We also studied two additional groups that consisted of the athletes who trained in the conditions of middle-altitude and students after the performance of cognitive tasks. The total number of participants was 80. RESULTS: The results obtained revealed both general patterns and differences in a body`s adaptational response in various group subjects studied. A general sign of the participants` adaptation is rhythmical changes in psychophysiological parameters with the alternation of differently directed phases of these changes both for the bioelectrical processes and vegetative functions of the body. The electrophysiological analysis revealed that differences in the character of adaptational changes depend on synchronization patterns in the cortex of cerebral hemispheres (localization, periodicity, frequency, alpha rhythm amplitude, etc.). These patterns are connected with the specificity of training loads. CONCLUSIONS: As a result of the study we made a conclusion that synchronization plays a crucial role in body`s adaptation processes and a further longitudinal research is needed on individual and age-related peculiarities between the bioelectrical activity of the brain and adaptational changes in the body.